ANALISIS DETERMINAN PENDAPATAN NELAYAN: (STUDI KASUS: NELAYAN JARING INSANG DI KELURAHAN PANTAI AMAL KOTA TARAKAN PROVINSI KALIMANTAN UTARA) - Rizky Agusriyanti; Charitin Devi; Ferrica Christinawati Putri; Kartini Kartini; Meylin Rahmawati; Nursia Nursia; Sulistya Rini Pratiwi; Yohanna Thresia Nainggolan (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2023)
This research was carried out in the coastal area in the Amal Beach Village. The purpose of this research is to find out some of the determinations that influence the income of gill net fishermen in Pantai Amal Village. The approach used in this study is a quantitative descriptive approach with modeling using multiple linear regression. Determination of the sample in this study using purposive sampling. The results showed that there was a simultaneous effect on the variables of working capital, length of time at sea and experience on the income of gill net fishermen in Pantai Amal Village. While the variables of working capital, labor, length of time at sea and experience have a simultaneous effect on the income of gill net fishermen in Pantai Amal Village.